Performance Evaluation of Microscanner Plus, an Automated Image-Based Cell Counter, for Counting CD4+ T Lymphocytes in HIV Patients - Woong Sik Jang; Junmin Lee; Seoyeon Park; Chae Seung Lim; Jeeyong Kim (Diagnostics, 2023)
Counting CD4+ T lymphocytes using flow cytometry is a standard method for monitoring patients with HIV infections. Simpler and cheaper alternatives to flow cytometry are in high demand because getting access to flow cytometers is difficult or impossible in resource-limited settings. We evaluated the performance of the Microscanner Plus, a simple and automated image-based cell counter, in determining CD4 counts against a flow cytometer. CD4 count results of the Microscanner Plus and flow cytometer were compared using samples from 47 HIV-infected patients and 87 healthy individuals. All CV% for precision and reproducibility tests were less than 10%. The Microscanner Plus’s lowest detectable CD4 count was determined to be 15.27 cells/µL of whole blood samples. The correlation coefficient (R) between Microscanner Plus and flow cytometry for CD4 counting in 134 clinical samples was very high, at 0.9906 (p < 0.0001). The automated Microscanner Plus showed acceptable analytical performance for counting CD4+ T lymphocytes and may be particularly useful for monitoring HIV patients in resource-limited settings.